Mineral and Bone Metabolism Markers and Mortality in Diabetic Patients on Haemodialysis - Martín-Carro, B (2023)
Background: Diabetic patients on haemodialysis have a higher risk of mortality than non-diabetic patients. The aim of this COSMOS (Current management of secondary hyperparathyroidism: a multicentre observational study) analysis was to assess whether bone and mineral laboratory values [calcium, phosphorus and parathyroid hormone (PTH)] contribute to this risk. Methods: COSMOS is a multicentre, open-cohort, 3-year prospective study, which includes 6797 patients from 227 randomly selected dialysis centres in 20 European countries. The association between mortality and calcium, phosphate or PTH was assessed using Cox proportional hazard regression models using both penalized splines smoothing and categorization according to KDIGO guidelines. The effect modification of the association between the relative risk of mortality and serum calcium, phosphate or PTH by diabetes was assessed. Results: There was a statistically significant effect modification of the association between the relative risk of mortality and serum PTH by diabetes (P = .011). The slope of the curve of the association between increasing values of PTH and relative risk of mortality was steeper for diabetic compared with non-diabetic patients, mainly for high levels of PTH. In addition, high serum PTH (>9 times the normal values) was significantly associated with a higher relative risk of mortality in diabetic patients but not in non-diabetic patients [1.53 (95% confidence interval 1.07-2.19) and 1.17 (95% confidence interval 0.91-1.52)]. No significant effect modification of the association between the relative risk of mortality and serum calcium or phosphate by diabetes was found (P = .2 and P = .059, respectively). Conclusion: The results show a different association of PTH with the relative risk of mortality in diabetic and non-diabetic patients. These findings could have relevant implications for the diagnosis and treatment of chronic kidney disease-mineral and bone disorders.